Village Fund for Peatlands Restoration: Study of Community’s Perceived Challenges and Opportunities in Muaro Jambi District - Sujai, Mahpud; Mizuno, Kosuke; Soesilo, Tri Edhi Budhi; Wahyudi, Riko; Haryanto, Joko Tri (Forest and Society, 2021)
Peatlands conversion to dryland for plantation has caused environmental havoc and is more prone to natural disasters in Indonesia. Community engagements under village administration should be the main strategy for supporting peatlands restoration. Since the new law on villages was enacted in 2014, the village has gained authority and delegated responsibilities from the upper-level government to make rural development decisions in various sectors, including those connected to environmental management, such as peatland restoration. The recognition of authority is followed by the transfer of significant funds, called village funds, from the central government as a form of commitment to undertake the village law. Currently, applied regulations allow community engagement to utilize the village fund for supporting peatland restoration. This study investigated the community's perceptions of village fund utilization for peatland restoration through in-depth interviews and questionnaires with site-level stakeholders that influence village budget allocation-related policies. The investigated aspects included village budgeting and development planning mechanism, the capacity of the community, and rules of district government in supervising the villages. Based on our findings, the identified challenges include the absence of environmental aspects as a part of village development pillars for developing village planning and budgeting, lack of community's environmental-economical nexus knowledge, and lack of district government in supervising village fund utilization and management at the site-level. However, the opportunities to direct the village fund utilization for peatlands restoration are widely open by strengthening the roles of district government to improve village fund governance at the site level.